Medical apology at a crossroad: a need for the enactment of apology legislations - Jahn Kassim, Puteri Nemie; Saleh, Muhammad Ridhwan; Mohamed, Duryana (Lexis Nexis, 2019)
Apologising has always been viewed as an important social conduct that allows for closure in disputes. The aftermath of disputes and conflicts are usually fuelled with feelings of anger, injustice, mistrust and a tendency to sue. Apologies can be made through statements of regret and empathy, acceptance of responsibility as well as proper explanation of the events leading to the mishap, hence, the severity of the aftermath situations can be significantly reduced. Further, studies have shown that apologising after a medical mishap can also be effective in a dispute resolution mechanism by healing and preserving relationships as well as triggering settlement negotiations. However, medical practitioners are rather hesitant to apologise after the occurrence of adverse events fearing that this may be treated as an ‘admission of guilt’ and any statements made at this point may be admissible in judicial proceedings as evidence of fault or liability. In Malaysia, the adverse effect of ‘medical apology’, became apparent from the outcome of two medical negligence cases, namely, Gurmit Kaur a/p Jaswant Singh v Tung Shin Hospital & Anor[2012] 4 MLJ 260; [2013] 1 CLJ 699 and Norizan bt Abd Rahman v Dr Arthur Samuel [2013] 9 MLJ 385. In both of these cases, the apology given by the medical practitioners was construed as admissions of guilt and used in establishing liability. Thus, the negative implications of apology needs to be addressed in Malaysia so as to preserve the immense benefits of apology, particularly, in medical negligence disputes. Lessons can be learned from several jurisdictions around the globe that have enacted ‘Apology Laws’ to explicitly preclude ‘medical apologies’ made after adverse events from being treated as admission of fault or as evidence to prove liability. This has been considered beneficial in preserving the effectiveness of apologies within the parameters of a protective legislation.